Pediatric renal trauma: 17 years of experience at a major Scandinavian trauma center - Paal Aksel Naess; Christine Gaarder; Amund Hovengen Ringen; Nils Oddvar Skaga; André Fatland (Trauma Surgery & Acute Care Open, 2023)
Background Children are at increased risk of renal injuries from blunt trauma due to their anatomic constitution. The kidney is injured in 5–20% of pediatric patients with blunt abdominal trauma. During the last decades, the management of pediatric renal injuries has evolved toward non-operative management (NOM) unless the patient is hemodynamically compromised. The aim of the present study was to assess contemporary treatment strategies and evaluate outcomes in pediatric patients with renal injuries admitted to a major Scandinavian trauma center.Methods A retrospective cohort study of all trauma patients under 18 years admitted to our institution from January 1, 2003 to December 31, 2019 with main focus on patients with renal injury. Outcomes for two time periods were compared, 2003–2009 (Period 1; P1) and 2010–2019 (Period 2; P2), and the study cohort was also stratified into age groups, survivors and non-survivors and severity of renal injury.Results In total, there were 4230 pediatric patients included in Oslo University Hospital Trauma Registry during this 17-year period and of these 115 (2.7%) had a renal injury. Nephrectomy was performed in four (3.5%) of the patients, angiographic embolization five (4.3%) and ureteral stent placement was performed in six patients (5.2%) due to urinary extravasation. Seven patients died, implying a crude mortality of 6.1%, with one exception secondary to traffic-related incidents. None of the deaths were attributed to renal injury and mortality fell to 1.2% in P2.Discussion This study on contemporary pediatric renal trauma care is one of the largest from a single institution outside the USA. Our results clearly show that NOM, including minimally invasive procedures in selected cases, is achievable in more than 90% of cases with low mortality and morbidity.Level of evidence Level IV.